Crime Analysis Case Studies - Greg Jones and Mary Malina (My University, 2016)
Crime analysis has gained significant momentum within the law enforcement community in the past decade. Many agencies have employed highly skilled analysts who contributed to the apprehension of criminal offenders and identification of important crime patterns and trends. Agencies have also benefited by the increased efficiency and effectiveness of analytical support to aid police in areas such as robbery, homicide, and burglary. With sustained support from leadership, crime analysts can provide useful and informative products that enhance police operations. This publication from the Police Foundation’s Crime Mapping and Problem Analysis Laboratory provides practical examples from four very different communities that showcase the utility of crime analysts and the type of analyses that can be achieved given the proper training, skills, and leadership